ERKIN VAHIDOV’S SKILL OF EXPRESSING THE NATIONAL SPIRIT THROUGH COMICS AND CHARACTERS - Halima Yuldasheva (European Journal of Humanities and Educational Advancements, 2023)
The article analyzes the skill of expressing the national spirit through comic images and characters on the example of Erkin Vahidov’s series "Wise Village Anecdotes". This series is not just a form of funny narratives put into verse, but the poet’s purpose is to raise the spirits of his compatriots in the conditions of tyranny, to express unspeakable truths, and at the same time, to treat the vices and defects of the character of his contemporaries through laughter, sarcasm, and humor. It is proved by means of examples that the intention to do is expressed